Comparative Study Between Clean Intermittent Self-Catheterization (Cisc) and Continuous Indwelling Catheterization (Cidc) in Relieving Acute Refractory Retention of Urine Due to Benign Enlargement of Prostate (Bep) (Bangladesh Journal of Urology, 2020)
Objective: To compare the clean intermittent self-catheterization (CISC) with continuous indwelling catheterization (CIDC) in relieving acute urinary retention (AUR) due to benign enlargement of prostate (BEP). Materials and Methods :A total 60 patients attending in urology department of Dhaka Medical college hospital were included according to inclusion criteria ,Patients were randomized by lottery into two groups namely group –A and group –B for CISC and IDC drainage respectively . Thus total 60 patients 30 in each group completed study.Results : Most men can safely be managed as out-patients after AUR due to BPH. The degree of mucosal congestion and inflammation within the bladder was found to be lower in those using CISC and the bladder capacity in these patients was also found higher.Patients with an IDC had a high incidence of UTIs then that of patients with CISC. During the period of catheterization the incidence of UTI was 43.3% in group B in comparison to 40% in group A; before TURP 36% in group B in comparison to 10% incidence in group A.According to patient’s opinion CISC is better than IDC in the management of AUR. Experiencing bladder spasm, reporting blood in urine, management difficulties, incidence and severity of pain were less in CISC group, and the method of CISC was well accepted by patients as well as their family members.Conclusion: From the current study it may be suggested that CISC is better technique for management of AUR patient due to BPH than IDC. It can also be very helpful when surgery must be delayed or avoided due to any reasons in this group of patients.Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.105-110